Enhanced luminescence of Tb3+/Eu3+ doped tellurium oxide glass containing silver nanostructures - Kassab, Luciana R. P. [UNESP]; de Almeida, Ricardo; da Silva, Davinson M.; de Assumpcao, Thiago A. A.; de Araujo, Cid B. (American Institute of Physics (AIP), 2009)
We report on energy transfer studies in terbium (Tb3+)-europium (Eu3+) doped TeO2-ZnO-Na2O-PbO glass containing silver nanostructures. The samples excitation was made using ultraviolet radiation at 355 nm. Luminescence spectra were recorded from approximate to 480 to approximate to 700 nm. Enhanced Eu3+ luminescence at approximate to 590 nm (transition D-5(0)-F-7(1)) and approximate to 614 nm (transition D-5(0)-F-7(2)) are observed. The large luminescence enhancement was obtained due to the simultaneous contribution of the Tb3+-Eu3+ energy transfer and the contribution of the intensified local field on the Eu3+ ions located near silver nanostructures.
Keywords: doping; europium compounds; glass; lead compounds; nanostructured materials; photoluminescence; silver compounds; sodium compounds; tellurium compounds; terbium compounds; ultraviolet radiation effects; zinc compounds